2004
DOI: 10.1590/s0073-47212004000400010
|View full text |Cite
|
Sign up to set email alerts
|

Protein content and electrophoretic profile of fat body and ovary extracts from workers of Melipona quadrifasciata anthidioides (Hymenoptera, Meliponini)

Abstract: ABSTRACT. Workers of Melipona quadrifasciata anthidioides (Lepeletier, 1836) develop their ovaries and lay eggs, therefore the production of vitellogenin is expected. In electrophoretic profiles only fat body extracts from nurse workers and ovary extracts from newly-emerged workers show protein with molecular mass similar to vitellogenin. However, an increase in the protein content was detected in forager fat body. This increase was attributed to storage of vitellogenin or other proteins in the previous phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Firstly, it is in close proximity to the heart, ostia, and body cavities. Secondly, according to Paes de Oliveira and Cruz-Landim 37 , it is in the trophocytes that vitellogenin is synthesized, the concentration of which is most probably the highest in the third tergite from where it is immediately directed to the appropriate tissues by the circulatory system. This solution enables a rapid distribution of these substances and ensures the queenְ’s reproductive dominance 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it is in close proximity to the heart, ostia, and body cavities. Secondly, according to Paes de Oliveira and Cruz-Landim 37 , it is in the trophocytes that vitellogenin is synthesized, the concentration of which is most probably the highest in the third tergite from where it is immediately directed to the appropriate tissues by the circulatory system. This solution enables a rapid distribution of these substances and ensures the queenְ’s reproductive dominance 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fat bodies accumulate toxic and reserve compounds (e.g. urea, uric acid) 37 and protect against oxidative stress, enhancing the apian resistance systems 38 – 41 . Roma et al 42 suggest that a few modifications had occurred during the evolution of the insects in the cells of the fat body, which resulted in the functional specialization of the individuals.…”
Section: Introductionmentioning
confidence: 99%
“…rufa along with senescence processes, in May and June. Cruz-Landim [ 39 ] and Paes de Oliveira and Cruz-Landim [ 31 ] confirmed that it was these proteins and other compounds, including antioxidants and proteases, that were synthetized in these specific cells.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, fat bodies accumulate toxic and reserve compounds [e.g. urea, uric acid; [ 31 ]] and protect against oxidative stress, enhancing the apian resistance systems, as well as having effect on overwintering and post-wintering performance [ 32 – 35 ]. They actively participate in vitellogenesis [ 36 – 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation